2014
DOI: 10.3389/fnhum.2014.00192
|View full text |Cite
|
Sign up to set email alerts
|

Cultural influences on social feedback processing of character traits

Abstract: Cultural differences are generally explained by how people see themselves in relation to social interaction partners. While Western culture emphasizes independence, East Asian culture emphasizes interdependence. Despite this focus on social interactions, it remains elusive how people from different cultures process feedback on their own (and on others') character traits. Here, participants of either German or Chinese origin engaged in a face-to-face interaction. Consequently, they updated their self- and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 59 publications
(133 reference statements)
5
29
2
1
Order By: Relevance
“…Additionally, one factor that could influence our results is culture. Previous studies indicated that there were cultural differences, not only behavioral but also neural, in self-referential processing (Zhu et al, 2007 ; Korn et al, 2014 ; Ma et al, 2014 ). SRE is known to be relatively robust across cultures, but it is possible to show different results between participants from different cultural backgrounds (for example, Westerner vs. East Asian) when they perform referential and recognition tasks, especially in the comparison between self and close-other, for example, a parent or friend.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, one factor that could influence our results is culture. Previous studies indicated that there were cultural differences, not only behavioral but also neural, in self-referential processing (Zhu et al, 2007 ; Korn et al, 2014 ; Ma et al, 2014 ). SRE is known to be relatively robust across cultures, but it is possible to show different results between participants from different cultural backgrounds (for example, Westerner vs. East Asian) when they perform referential and recognition tasks, especially in the comparison between self and close-other, for example, a parent or friend.…”
Section: Discussionmentioning
confidence: 98%
“…An interesting question for future research is whether people tend to weigh negative vs positive social information differently in appraisals of facial beauty. In a recent fMRI study, Korn et al (2014) offered evidence that, across cultures, evaluations of character traits are more amenable to positive ( vs negative) social information. Such findings support the possibility that positive vs negative social information is accorded varying levels of significance in shaping one’s judgments of attractiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Note, we distinguish between the observed behaviour (conformity) and whether this behaviour was elicited by the available information (adaptive response) or a general norm whereby following the majority is the socially desirable behaviour. There are clear cultural differences in the strength of these majority influences [53,54].…”
Section: Normative Influences On Conformitymentioning
confidence: 99%